2014
DOI: 10.4103/0019-5154.131374
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 expression in different types of psoriatic lesions: Analysis of 66 cases

Abstract: Background:Caveolin-1 is a key structural and functional protein. Caveolin-1 is known to modulate multiple signal-transducing pathways involved in cell differentiation and proliferation. Psoriasis is viewed as a multifactorial pathology characterized by keratinocyte hyperproliferation and abnormal cell maturation.Objectives:To examine the expression of caveolin-1 in skin biopsies from normal subjects, patients, and subjects with the three respective isoforms of psoriasis (psoriasis vulgaris, localized pustular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In the current work, the intensity of Cav‐1 immunohistochemical staining showed significant reduction in psoriatic plaques when compared to the apparently normal skin of psoriatic patients as well as normal control skin of healthy volunteers, which signifies its evident role in disease pathogenesis. These results agreed with those of several previous studies 7–10 that reported marked Cav‐1 downregulation in psoriatic lesions than normal healthy skin. Zhang et al, 7 suggested that reduction of Cav‐1 may encourage certain cellular and biochemical alterations triggering psoriasis, for example; (i) stimulation of mitotic divisions of basal keratinocytes with acceleration of epidermal turnover, leading to excessive epidermal hyperplasia, (ii) activation of anti‐apoptotic mechanisms, and/or (iii) inhibition of intracellular Ca 2 + mobilization, resulting in impairment of keratinocyte differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current work, the intensity of Cav‐1 immunohistochemical staining showed significant reduction in psoriatic plaques when compared to the apparently normal skin of psoriatic patients as well as normal control skin of healthy volunteers, which signifies its evident role in disease pathogenesis. These results agreed with those of several previous studies 7–10 that reported marked Cav‐1 downregulation in psoriatic lesions than normal healthy skin. Zhang et al, 7 suggested that reduction of Cav‐1 may encourage certain cellular and biochemical alterations triggering psoriasis, for example; (i) stimulation of mitotic divisions of basal keratinocytes with acceleration of epidermal turnover, leading to excessive epidermal hyperplasia, (ii) activation of anti‐apoptotic mechanisms, and/or (iii) inhibition of intracellular Ca 2 + mobilization, resulting in impairment of keratinocyte differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…These results agreed with those of several previous studies 7–10 that reported marked Cav‐1 downregulation in psoriatic lesions than normal healthy skin. Zhang et al, 7 suggested that reduction of Cav‐1 may encourage certain cellular and biochemical alterations triggering psoriasis, for example; (i) stimulation of mitotic divisions of basal keratinocytes with acceleration of epidermal turnover, leading to excessive epidermal hyperplasia, (ii) activation of anti‐apoptotic mechanisms, and/or (iii) inhibition of intracellular Ca 2 + mobilization, resulting in impairment of keratinocyte differentiation. Yamaguchi et al, 9 proposed that Cav‐1 reduction in psoriatic lesions can augment keratinocyte hyperproliferation via stimulation of the JAK/STAT3 signalling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Loss of caveolin-1 in epidermal keratinocytes has been shown to contribute to the development of psoriasis. 36 , 37 , 38 , 39 Therefore, we evaluated whether rhododendrin also regulates caveolin-1 expression. Surprisingly, caveolin-1 expression was found to be preserved with downregulation of TLR-7 upon treatment with rhododendrin compared with keratinocytes treated with IMQ alone, suggesting that rhododendrin exerts a critical therapeutic action in the maintenance of skin homeostasis during disease pathogenesis ( Figures 5a and b ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the expression level of caveolin-1 is strikingly decreased and its spatial pattern of expression is altered in psoriatic skin. 36 , 37 , 38 , 39 Considerable work has been done to correlate caveolin-1 expression and the activity of receptor kinases with their respective downstream effects. 44 Activation of receptor tyrosine kinases and of the downstream p42/p44 MAP kinase pathway has been implicated in the keratinocyte hyperproliferation that is commonly associated with the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional histological features of EP include some features of classical psoriasis, including parakeratosis, acanthosis, spongiosis, Munro micro-abscesses, and occasional apoptotic keratinocytes. 13 , 15 , 16 However, due to exfoliation and loss of the epidermal stratum corneum in EP, Munro micro-abscesses and parakeratosis may not be prominent histologically. 13 Furthermore, in order to confirm a diagnosis of EP, clinicians must rule out other plausible causes of erythroderma such as atopic dermatitis, pityriasis rubra pilaris, drug eruptions, contact dermatitis, seborrheic dermatitis, immunobullous disorders, connective tissue disorders, and Sezary syndrome and other malignancies.…”
Section: Clinical Features and Presentationmentioning
confidence: 99%